Rice stripe virus: Exploring Molecular Weapons in the Arsenal of a Negative-Sense RNA Virus - Xu, Yi; Fu, Shuai; Tao, Xiaorong; Zhou, Xueping (Annual review of phytopathology, 2021)
Rice stripe disease caused by Rice stripe virus (RSV) is one of the most devastating plant viruses of rice and causes enormous losses in production. RSV is transmitted from plant to plant by the small brown planthopper (Laodelphax striatellus) in a circulative-propagative manner. The recent reemergence of this pathogen in East Asia since 2000 has made RSV one of the most studied plant viruses over the past two decades. Extensive studies of RSV have resulted in substantial advances regarding fundamental aspects of the virus infection. Here, we compile and analyze recent information on RSV with a special emphasis on the strategies that RSV has adopted to establish infections. These advances include RSV replication and movement in host plants and the small brown planthopper vector, innate immunity defenses against RSV infection, epidemiology, and recent advances in the management of rice stripe disease. Understanding these issues will facilitate the design of novel antiviral therapies for management and contribute to a more detailed understanding of negative-sense virus-host interactions at the molecular level.Rice stripe disease caused by Rice stripe virus (RSV) is one of the most devastating plant viruses of rice and causes enormous losses in production. RSV is transmitted from plant to plant by the small brown planthopper (Laodelphax striatellus) in a circulative-propagative manner. The recent reemergence of this pathogen in East Asia since 2000 has made RSV one of the most studied plant viruses over the past two decades. Extensive studies of RSV have resulted in substantial advances regarding fundamental aspects of the virus infection. Here, we compile and analyze recent information on RSV with a special emphasis on the strategies that RSV has adopted to establish infections. These advances include RSV replication and movement in host plants and the small brown planthopper vector, innate immunity defenses against RSV infection, epidemiology, and recent advances in the management of rice stripe disease. Understanding these issues will facilitate the design of novel antiviral therapies for management and contribute to a more detailed understanding of negative-sense virus-host interactions at the molecular level.